STUDY THE ROLE OF PLASMIDS OF SOME BACTERIAL ISOLATES TO SOME ANTIBIOTICS. - LAITH M. NAJEEB (مجلة جامعة الانبار للعلوم الصرفة, 2012)
Thes study involved bacterial curing plasmids of four isolates, three isolates belonging to the genus E.coli with local numbers 1, 2 and one to Klebsiella pneumonia and isolation Raoultcella planticola (Klebsiella planticola) . the study includ test the role of these plasmids in the response of isolates to various antibiotics and to achieve the grown isolates at differant temperatures different incubation periods until killing ratio of 95% these bacteria scrubbed isolates remaining, then the use of technology DNA Electrophoresis was detected diffraction plasmids compared with the original; way drive tested the sensitivity of the original isolates and neutralized to various antibiotics neutralized isolates appeared more sensitive to antibiotics, especially towards Relenza Rifampin (RA) and Tobramycin (TOB), where isolates curing emerged of the type E. coli with local numbers 1.2 sensitive to inhibition at 8, 8.3 mm, respectively, with the number 3 is sensitive to anti-RA inhibition rate of 9 mm, while the original isolates were not sensitive to these antibiotics.